2012
DOI: 10.1016/j.kjms.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Essentiality of HIV testing and education for effective HIV control in the national pilot harm reduction program: The Taiwan experience

Abstract: In 2005, a national pilot harm reduction program (PHRP), which mainly included a methadone maintenance treatment program (MMTP) and a needle/syringe exchange program (NSP), was implemented in Taiwan. We conducted this study to evaluate the effectiveness of harm reduction measures on HIV control among injecting drug users (IDUs) between PHRP and nonPHRP. The data on HIV, collected from incumbent Taiwanese authorities, were analyzed for their associations, risk and protective factors with PHRP measures. While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Many Taiwan IDUs had an experience of sharing needles or dilution water, and the HIV prevalence among IDUs reached a peak in 2005 [35, 36]. However, many antiretroviral agents [18, 19] have been investigated as CYP3A4, 2B6, or 2D6 strong inducers or inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Taiwan IDUs had an experience of sharing needles or dilution water, and the HIV prevalence among IDUs reached a peak in 2005 [35, 36]. However, many antiretroviral agents [18, 19] have been investigated as CYP3A4, 2B6, or 2D6 strong inducers or inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, to encounter the escalating IDUs and HIV infections through needle sharing, the first MMTPs were implemented in July 2006 [35, 36]. However, a thorough evaluation on the treatment responses of a MMTP has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…To address the escalating IDU and HIV infections through needle-sharing, the first MMTPs were implemented in July 2006 [38,39]. Because of this new measure, it is especially important for medical professionals to understand the comprehensive effects of MDIs among MMTP patients to inform treatment planning and care management.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, heroin and methamphetamine have been the predominant illicit drugs since 1990s, with an increasing trend of illegal ketamine use . Since 2005, due to the escalating HIV incidences among the injection drug users, the national harm reduction program (HRP) was implemented . The measures of HRP mainly included methadone maintenance treatment program (MMTP) and needle exchange program (NEP) .…”
Section: Introductionmentioning
confidence: 99%
“…The measures of HRP mainly included methadone maintenance treatment program (MMTP) and needle exchange program (NEP) . We have previously shown that education and HIV testing were essential for the effective HIV control among injecting heroin users . However, the factors contributing to such outcomes other than education remain to be scrutinized, especially at the local levels .…”
Section: Introductionmentioning
confidence: 99%